From hashtags to healing: Social media insights on kinesio taping in Türkiye: Social media insights on kinesio taping - Temel, Mustafa Hüseyin; Bağcıer, Fatih (Journal of Surgery and Medicine, 2025)
Background/Aim: Social media provides valuable insights into healthcare practices, including kinesio taping (KT), a technique used for pain relief and stability. Despite its popularity, there is limited research on KT content on social media. This study aims to analyze social media posts related to KT in Türkiye. Methods: The study was conducted by analyzing posts on social media platforms including Twitter, Instagram, Facebook, and YouTube. The hashtags ‘#kinezyobant’, ‘#kinezyobantlama’, and ‘#kinezyoteyp’, as well as the keywords ‘kinezyobant’, ‘kinezyobantlama’, and ‘kinezyoteyp’ were used as search criteria. The collected data were categorized into different groups: healthcare organizations, commercial entities, physicians, news sources, users, and non-physician healthcare professionals. Results: A total of 445 posts related to KT were identified across various social media platforms. YouTube boasted the highest number of posts, followed by Twitter, Facebook, and Instagram. Non-physician healthcare professionals contributed the most posts, whereas physicians and news sources posted relatively less. Twitter saw the highest number of user-generated posts, while Instagram displayed a higher prevalence of posts for commercial purposes. Among all platforms, Facebook accounted for the highest number of posts by healthcare organizations. Conclusion: Social media platforms, especially YouTube, are crucial in disseminating information about KT. Non-physician healthcare professionals notably contribute to the online discourse, potentially highlighting the need for enhanced KT education among physicians. Facebook offers benefits for patients to communicate with and engage in healthcare organizations. However, addressing concerns about misinformation and privacy, along with promoting responsible usage of these platforms in healthcare, is crucial.